Performance Analysis of Indian Agriculture Extension System - Rakesh Sharma, (Indian Journal of Extension Education, 2018)
An understanding of the evolution of the system and its contemporary structure is of great significance as it helps us to understand the dynamics of the system. This paper presents an analysis of agricultural extension system in India which is based on NSSO 59th round (2003) and 70th round (2013) survey. The study revealed that only 41 per cent farmers' households in 2003 and 35 percent farmers' households in 2013 accessed agricultural knowledge from any source. So it is essential that public sector extension system should be improving its performance in terms of knowledge acquisition and access to farmers.